Shaving: a simple and effective treatment for moderate congenital hypertrichosis - Plantin, P; Schoenlaub, P; Dupré, D; Le Fur, J M (EJD. European journal of dermatology, 1998)
Congenital hypertrichosis is a rare disorder. It is sometimes associated with facial dysmorphism, and dental and gingival abnormalities. This condition constitutes an esthetic problem and regular shaving with a simple razor can be a simple method of treatment.